Pengujian Kinerja Pompa Sentrifugal Menggunakan Kontrol Inventer - Wahyu Djalmono Putro (Universitas Muhammadiyah Yogyakarta, 2010)
An alternative method for obtaining data on pump discharge and head in order enable to determine pump characteristics has been investigated and formulated. Three types of centrifugal pump, the snails house, diffuser and turbine, have been selected. According to their respective manufacturers, the heads of these pumps are 16 m, 11 m and 9 m, respectively; their respective debits are 105 m3/h, 105 m 3/h and 150 m3/h; and their respective efficiencies are 95 %, 70 % and 95 %. Two testing parameters, shaft rotation and ball valve opening portion have been considered. Five different rotations, 1500 rpm, 1750 rpm, 2000 rpm, 2500 rpm and 2800 rpm, and seven different ball valve opening portions, 0 %, 25 %, 30 % 45 %. 60 %, 75 % and 100 %, have been considered. The main units of the alternative methods for measuring pump discharge and head are an electric motor, an inventer, a U-tube manometer and an orifice. The result shows that the heads the pumps are 15,4 m,11,45 m and 9,7 m, respectively, the debits of the pumps are 103 m3/h, 108 m 3/h and 171 m3/h, and efficiency are 98 %, 69,5 % and 97,5 %, respectively. Controlled inventer method can be used as one of the alternative pump performance test.